Enterotoxin gene profile of Staphylococcus aureus isolates recovered from bovine milk produced in central Ethiopia - Eyasu Tigabu Seyoum; Tesfu Kassa Mekonene; Daniel Asrat Woldetsadik; Bayleyegn Molla Zewudie; Wondwossen Abebe Gebreyes (Journal of Infection in Developing Countries)
Introduction: Staphylococcal food intoxication is dependent on the production of enterotoxins, the single most important virulence factors. Various studies conducted in Ethiopia have depicted the prevalence of S. aureus in bovine milk. However, there is no published data regarding the enterotoxin gene profile of S. aureus isolates in Ethiopia. The aim of this study was, therefore, to evaluate enterotoxin gene carriage profile of S. aureus isolates recovered from bovine milk samples from central Ethiopia. Methodology: In this study, 109 S. aureus isolates recovered from bovine milk were analyzed for carriage of the classical enterotoxin genes. Genomic DNA extraction was performed using a commercially available kit. Two sets of multiplex polymerase chain reaction (PCR) assays were used to detect the five classical enterotoxin-coding genes and the toxic shock syndrome toxin gene. Results: At least one type of S. aureus enterotoxin gene (SE) was carried in 73 (66.9%) of the isolates. The most frequently encountered gene was sea (40; 36.7%) followed by seb (19; 17.4%), see (18; 16.5%), tst (16; 14.7%), sec-1 (12; 11.01%), and sed (7; 6.4%). Of the 73 S. aureus isolates harboring at least one of the enterotoxin genes, 26 (35.6%) strains harbored more than one enterotoxin gene. Conclusions: More than half of the S. aureus isolates harbored at least one of the enterotoxin coding genes, indicating milk specimens contaminated by S. aureus could have a high chance of causing food intoxication.